Bridging the gap between scientific research and parental concerns on children language development - Annick De Houwer; Anna Ghimenton; Amelia Lambelet (Babylonia)
Since its founding in 1991, Babylonia has aimed to bridge the gap between scientific research and language education practice. Most of our issues have been addressed to language teachers and teacher trainers. With this special issue, we want to widen our mission and provide accessible, evidence-based answers to parents and caregivers of young children.